Phase structure of the Polyakov-quark-meson model - Schaefer, Bernd-Jochen; Pawlowski, Jan M.; Wambach, Jochen (Physical review. D, Particles, fields, gravitation, and cosmology, 2007)
The relation between the deconfinement and chiral phase transition is explored in the framework of a Polyakov-loop-extended two-flavor quark-meson (PQM) model. In this model the Polyakov loop dynamics is represented by a background temporal gauge field which also couples to the quarks. As a novelty an explicit quark chemical potential and Nf-dependence in the Polyakov loop potential is proposed by using renormalization group arguments. The behavior of the Polyakov loop as well as the chiral condensate as function of temperature and quark chemical potential is obtained by minimizing the grand canonical thermodynamic potential of the system. The effect of the Polyakov loop dynamics on the chiral phase diagram and on several thermodynamic bulk quantities is presented.
Gesehen am 06.12.2017